Bentuk Penyajian Dikia Rabano pada Acara Pesta Perkawinan di Kenagarian Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan - Teguh Kurniawan Abdi; Yensharti Yensharti (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to describe the form of presentation of Dikia Rabano at the Wedding Party in Kenagarian Inderapura, Pancung Soal District, South Coast Regency. This type of research is qualitative using descriptive analytical data processing methods. The research instrument is the researcher himself and is assisted by stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are classifying data, clarifying data, analyzing data, describing data and concluding data. The results of the study show that the procession of presenting Dikia Rabano has 3 forms, namely: the implementation of the Mamak thanksgiving, in the Mamak thanksgiving, the presentation of Dikia Rabano is only performed seated by the Alim Ulama using verses of assalamualaika (barzanji). And in the implementation of Maarak Nasi Sapek from Induak Bako and Maarak Anak Daro jo Marapulai, this is shown standing while walking in a procession using the recitation of wasyahadu verses. Dikia Rabano music player is a person who is from 40 to 70 years old. The songs performed were 2 songs, namely Assalamualaika and Wasyahadu